(untitled) (Medical Forum Monthly, 2020)
Objective: To evaluate the perception of the students about CBL in clinical subjects. Study Design: Cross Sectional study. Place and Duration of Study: This study was conducted at the Al-Tibri Medical College and Hospital, between January 2019 and October 2019. Materials and Methods: A total of 150 numbers of students, 50 from different disciplines like Gynae & Obstetrics, Ophthalmology, and ENT, were included on the bases of convenient sampling. After taking ethical approval, the data was collected through a well-designed questionnaire with the students' verbal consent. At the end of the clinical posting, the questionnaire was filled, and data was presented in the form of frequency and percentage, Chi-square test was applied to evaluate the qualitative data through SPSS. The level of significance was taken P=<0.05. Results: Both genders participated. The study results showed no significant difference among the students of Gynae & Obstetrics. Ophthalmology and ENT about the acceptance of CBL is an optimal learning strategy and a well-adopted component of self-directed Learning, particularly in clinical reasoning and case solving. Conclusion: CBL (Case-Based Learning) is a widely accepted learning strategy and helps develop essential skills required to be an excellent clinician in the future. It is considered the gold standard for Learning and implementing in clinical sciences in the field of medicine early on in students' medical careers. The educationist should incorporate the CBL in their medical sciences curriculum for the development of clinical reasoning and problem-solving skills.